IMPLEMENTASI PROGRAM KREDIT WIRAUSAHA BANGKIT JADI JAWARA (WIBAWA) DI KOTA SEMARANG PADA TAHUN 2017-2019 - Bagas Kurnia Adi; Sulistiyowati - - (Journal of Politic and Government Studies, 2021)
ABSTRACT One of the efforts of the Semarang City Government to improve the welfare of the people of Semarang City through increasing the level of community productivity and   economic   independence   in   the   field   of   MSME   capital   is   through   the Entrepreneurial Credit Program Bangkit Jadi Jawara (Wibawa) facility which has the objective of being a business capital loan program with relatively light interest, namely amounting to 3% and managed by the Semarang City Government through the Semarang City Cooperatives and MSMEs Office together with the stakeholders of the Regional Public.  Companies  BPR Bank  Pasar  Semarang    City.  In this study,  the researchers  presented  an  overview  of  the  implementation  process  of  the  Wibawa Credit Program in Semarang City in 2019 through two perspectives, namely the implementers and the Semarang City MSMEs community as the policy target group. The research method used is descriptive qualitative with data collection techniques through interviews and documentation. The data that the researchers o btained were then processed through the Triangulation Method, theory and data sources. The findings in this study are that the process of carrying out the Wibawa Credit Program  in  Semarang  City  in  2019  requires  a  form of good  communication  and cooperation between the implementers and the Semarang City MSMEs community as a policy target group due to limited human resources so that there are still overlapping tasks. Scope of work because officers do not only serve assistance in one program. The phenomenon of credit problems in the Wibawa Credit Program is still encountered but the implementor cannot provide specific sanctions because there is no legal basis that regulates it. The conclusion that can be drawn from this research is that the first, the UMKM community is quite satisfied with the existence of the Wibawa Credit Program facility, secondly there is a need for a good form of cooperation between the policy implementers and the MSME community due to limited resources and thirdly there is no  legal basis which is clearly regulates sanctions for customers experiencing the phenomenon of credit problems. The suggestion that the researchers gave in this study was to involve the MSME community to help and cooperate in coordinating each of their MSME groups to be able to obtain the Wibawa Credit Program facilities and supervise their insurance, as well as to make a clear and appropriate legal foundation in imposing sanctions for customers. who experience the bad credit phenomenon.